Contemporary marketing 2006 - Boone, Louis E., author; Kurtz, David L., author (Australia : Thomson/ South-Western, 2006)
CONTEMPORARY MARKETING 2006 by Boone and Kurtz has proven to be the premier principles of marketing text and package since the first edition. With each edition, this best selling author team builds and improves upon past innovations, creating the most technologically advanced, student friendly, instructor supported text available. This value-priced paperback text continues to provide the most current and up-to-date content by including the most current coverage of topics such as one-to-one marketing, strategic planning, guerilla marketing, customer relationship management, and much more.
Pt. 1: Designing customer-oriented marketing strategies. Ch. 1. Marketing : creating satisfaction through customer relationships ; Ch. 2. Strategic planning and the marketing process ; App. Creating an effective marketing plan ; Ch. 3. The marketing environment, ethics, and social responsibility ; Ch. 4. E-commerce : marketing in the digital age -- Pt. 2: Understanding buyers and markets. Ch. 5. Consumer behavior ; Ch. 6. Business-to-business (B2B) marketing ; Ch. 7. Serving global markets -- Pt. 3: Target market selection. Ch. 8. Marketing research, decision support systems, and sales forecasting ; Ch. 9. Market segmentation, targeting, and positioning ; Ch. 10. Relationship marketing, customer relationship management (CRM), and one-to-one marketing -- Pt. 4: Product decisions. Ch. 11. Product and service strategies ; Ch. 12. Category and brand management, product identification, and new-product development -- Pt. 5: Distribution decisions. Ch. 13. Market channels and supply chain management ; Ch. 14. Direct marketing and marketing resellers : retailers and wholesalers -- Pt. 6: Promotional decisions. Ch. 15. Integrated marketing communications ; Ch. 16. Advertising and public relations ; Ch. 17. Personal selling and sales promotion -- Pt. 7: Pricing decisions. Ch. 18. Price concepts and approaches ; Ch. 19. Pricing strategies.
Includes bibliographical references and index.
In English text.
Keywords: Marketing